Design of Photocaged Puromycin for Nascent Polypeptide Release and Spatiotemporal Monitoring of Translation1. (4th February 2015) - Buhr, Florian; Kohl‐Landgraf, Jörg; tom Dieck, Susanne; Hanus, Cyril; Chatterjee, Deep; Hegelein, Andreas; Schuman, Erin M.; Wachtveitl, Josef; Schwalbe, Harald
Abstract: The antibiotic puromycin, which inhibits protein translation, is used in a broad range of biochemical applications. The synthesis, characterization, and biological applications of NVOC‐puromycin, a photocaged derivative that is activated by UV illumination, are presented. The caged compound had no effect either on prokaryotic or eukaryotic translation or on the viability of HEK 293 cells. Furthermore, no significant release of ribosome‐bound polypeptide chains was detected in vitro. Upon illumination, cytotoxic activity, in vitro translation inhibition, and polypeptide release triggered by the uncaging of NVOC‐puromycin were equivalent to those of the commercial compound. The quantum yield of photolysis was determined to be 1.1±0.2 % and the NVOC‐puromycin was applied to the detection of newly translated proteins with remarkable spatiotemporal resolution by using two‐photon laser excitation, puromycin immunohistochemistry, and imaging in rat hippocampal neurons.